Role of Acacia Catechu in Regulating Connective Tissue Components during Experimental Gastric Ulcer Healing - Uzma Waseem, Tayyaba Mahmud, Natasha Nadeem, Samia Shahbaz, Amina Liaqat, Ursula Akif, Musa Salman (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the healing properties of different doses of Acacia catechu on histopathological changes induced by aspirin in the stomach of adult albino rats. Methods: In an experimental study which was carried out at Postgraduate Medical Institute for a period of 21 days, forty-eight adult albino rats were included. The animals were divided into four groups by ballottement. Every group was further subdivided into three groups based on the day of sacrifice. BDH (British drug houses) provided Aspirin in powder form, and the bark of Acacia catechu was obtained from Government College University (Botany Department). The study was approved by institutional Ethical Review Committee. Results: Increased number of fibroblasts were seen in the groups taking acacia catechu, signifying healing, compared to aspirin only group. After applying one-way ANOVA, a statistically significant difference was observed among the groups on day 7 and day 14 (P-value <0.01*). However, on day 3, an insignificant difference was seen among the groups (P-value = 0.97). Conclusion: Acacia catechu has a protective role against aspirin-induced gastric injury, by inhibiting inflammation. Keywords: Fibroblast, Acacia catechu, ulcer, wound healing.